A design of high‐gain array antenna with novel metamaterial structures for millimeter‐wave femtocell implementation. Issue 6 (23rd March 2022) - Jadidi, Iman; Honarvar, Mohammad Amin; Saghirzadeh Darki, Behnam
Abstract: A novel method based on the metamaterial concept has been proposed to increase the gain of a planar array antenna without increasing the dimensions for millimeter‐wave femtocell implementation which can easily replace expensive macrocells. To implement the proposed method and present its advantages, 16 novel metamaterial unit‐cells named split cylinder metamaterial resonators (SCMRs) have been used to increase the gain of a millimeter‐wave two‐layer array antenna. The dimensions of each SCMR are equal to 0.067 mm 3 or 0.0001 λg 3, where λg is the guided wavelength at 27.5 GHz. Providing an effective metamaterial environment by the proposed SCMRs increases the gain of the antenna by more than 10 dB in the operating frequencies compared to a sample array antenna in which no metamaterial structures is used. The proposed SCMRs at frequencies of 24.5–32.5 GHz, with the creation of negative permeability and permittivity, have created a metamaterial environment. The frequency range covered by the proposed antenna is 26.5–28.5 GHz for millimeter‐wave femtocell applications. The average gain of the proposed antenna in the operating frequency band is equal to 17 dB. Also, the radiation efficiency at 27.5 GHz is 86%. The final dimensions of the proposed antenna are equal to 0.047 λg 3 at 27.5 GHz. To confirm the accuracy of the full‐wave simulation, the proposed two‐layer array antenna was fabricated and its characteristics were measured. There is an acceptable fit between the simulated and measured results. It should be noted that the most important advantage of the SCMR is the improvement of antenna performance without increasing the dimensions.